(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The car industry is one of India’s main drivers of economic development and a major player in global value chains. The development of this sector was driven by significant support from the Government, which helped to pave the way for the production sectors of India to be distinctive. Cars manufactured in the nation serve only to the needs of low- and middle-income people, which distinguish this industry from the other automotive countries. This study examines the political and infrastructural responsibilities of government and other allowable variables in expanding the automotive and automotive industries of India. In 2017, India became the fourth biggest automotive market in the world, and local and international demand for Indian cars continues to rise. Manufacturers are increasingly updating, digitizing and automating to satisfy their consumers (including electric cars) and remain in the lead of competition.